La aplicación de la pena en consideración a las circunstancias modificativas de la responsabilidad criminal. Criterios de determinación legal y factores de individualización judicial - Manuel Gallego Díaz (Revista Vasca de Administración Pública, 2010)
The norms of enforcement of sentences taking into account the extenuating circumstances on criminal liability provide the judge with criteria to help him/her to specify the generic criminal framework about the offense into a more restricted one or even a new one, inferior o superior, derived from the former. But when the sentence is exact and judicially individualized, the judge, in a discretional and reasoned form, will have to concretize the extension of the sentence considering every cirumstance regarding the fact and the guilty which had not been considered from the point of view of the wrongful, the guilt and the purposes of the sentence. For these purposes, the criteria stated in rule six, section 66.1 by Criminal Code, in case of lack of extenuating circumstances, are also applicable to other norms in coordination with the explicit and implicitily established assumptions.